ӘДЕБИЙ ЖАНРЛАРДЫҢ РАЎАЖЛАНЫЎ БАСҚЫШЛАРЫ - Матимов, Кошкарбай Генжебаевич (FAN va JAMIYAT, 2026)
The article discusses the stages of emergence, formation, and historical development of literary genres. The classification of genres and their intermingling with other genres is discussed based on theoretical works. Thus, within the framework of this intervention, genre trends emerged, leading to the emergence of works with philosophical content in response to the artistic demands of the work.